Cryptosporidium oocysts removal by upflow direct filtration : pilot scale assessment - Nascimento, Marcely Ferreira (2020)
Studies on the removal of Cryptosporidium oocysts by direct filtration suggested that high removal efficiencies (>3.0 log) can be achieved, but the vast majority of the studies focused on the assessment of downflow direct filtration. However, in comparison with downflow direct filtration, filters in upflow direct filtration systems use lower filtration rates, deeper stratified bed, and water flows from coarse to fine sand grain, which may improve the removal of oocysts. In this context, we evaluated the removal of Cryptosporidium oocysts using upflow direct filtration, on a pilot scale, to treat Paranoá Lake water (Brazil) seeded with Cryptosporidium oocysts. The experiments were conducted with raw water with low turbidity (3.2–5.7 NTU) and induced higher turbidity (28–30 NTU). Non-parametric statistical analysis was used to verify correlations between the filtered water values and removal of oocysts, particles, and turbidity. In general, no correlation was observed between the parameters analyzed, nor between their removals. The exception was the correlation between residual values of Cryptosporidium oocysts and particles of 2 to 7 µm during ripening, an aspect that needs further evaluation. Under stable operation, average removal of Cryptosporidium oocysts by upflow direct filtration was >3.87 log. During ripening, removal of oocysts was around 1 log lower.